2010
DOI: 10.1099/mic.0.039131-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Escherichia coli csgD promoter: interplay between five transcription factors

Abstract: Under stressful conditions in nature, Escherichia coli forms biofilms for long-term survival. Curli fimbriae are an essential architecture for cell-cell contacts within biofilms. Structural components and assembly factors of curli are encoded by two operons, csgBA and csgDEFG. The csgD gene product controls transcription of both operons. Reflecting the response of csgD expression to external stresses, a number of transcription factors participate in the regulation of the csgD promoter. Analysis of the csgD mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
184
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(192 citation statements)
references
References 79 publications
(135 reference statements)
4
184
0
Order By: Relevance
“…It has also been shown that IHF activates Pe transcription indirectly via the alleviation of H-NS-mediated repression (van Ulsen et al, 1996). Recent reports further reinforce the role of IHF in alleviating H-NS silencing in Vibrio cholerae (Stonehouse et al, 2008) and in the csgD operon of E. coli (Ogasawara et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…It has also been shown that IHF activates Pe transcription indirectly via the alleviation of H-NS-mediated repression (van Ulsen et al, 1996). Recent reports further reinforce the role of IHF in alleviating H-NS silencing in Vibrio cholerae (Stonehouse et al, 2008) and in the csgD operon of E. coli (Ogasawara et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…Also noteworthy is that the anti-silencer LeuO (also a global regulator of membrane function) (Shimada et al, 2011a) and CsgD (the master regulator of biofilm formation) (Ogasawara et al, 2010a(Ogasawara et al, , b, 2011 were regulated by BasR.…”
Section: Regulation Targets Of Bassr: Group 2 Genes For Modification mentioning
confidence: 99%
“…The BasR-binding site on the csgD promoter was determined by DNase I footprinting assay (see Fig. 4), and is mapped on the csgD promoter, on which more than 10 transcription factors associate at various positions, as determined by Ogasawara et al (2010aOgasawara et al ( , b, 2011.…”
Section: Factors Affecting Bassr Functionsmentioning
confidence: 99%
“…Integration host factor and H-NS, two DNAbending nucleoid proteins, with opposing effects on CsgD expression, contribute to csgD regulation by architectural changes and competition for overlapping binding sites in the intergenic promoter region. Integration host factor is a positive regulator of transcription that binds in two hot spots in the csgD promoter along with other transcription factors Ogasawara et al, 2010b). Although the effects of H-NS have not been fully defined, it has been shown that csgD is suppressed when H-NS is bound to a large region of the csgD promoter that contains both transcription factor-binding hot spots described by Osagawara (Olsén et al, 1993;Ogasawara et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%